Farming practice and land management at Knossos, Crete: New insights from δ13C and δ15N analysis of Neolithic and Bronze Age crop remains - Nitsch, E; Jones, G; Sarpaki, A; Hald, M; Bogaard, A (Archaeopress, 2019)
Neolithic agriculture in the Aegean encompassed a diverse spectrum of cereals and pulses (Halstead 1994; Valamoti and Kotsakis 2007), and plausibly entailed intensive management (i.e. with careful tillage, weeding, manuring and watering, as needed) on a small scale in order to achieve marginal surpluses that buffered households and communities against poor harvests (Halstead 1981, 1987, 1989). This model is supported by isotopic evidence for the manuring of cereals and pulses, and for preferential watering of the latter, at Neolithic sites in Greece and Bulgaria (Bogaard et al. 2013; Vaiglova et al. 2014a). The availability of labour ultimately limits the size of the surplus that can be attained under such a system. Linear B texts indicate that Late Bronze Age palatial urban centres in the Aegean were at least partly sustained by surpluses gained from more extensive low-input cultivation sponsored by palatial elites